Enhanced Photocatalytic Activity of π-Conjugated Pyridine Rings-Modified C3N4/BiBiOCl Z-Scheme Heterogeneous Material - Yang, Wei (Langmuir : the ACS journal of surfaces and colloids, 2023)
The enhanced photocatalytic properties of Z-Scheme BiBiOCl/C3N4-DPY heterojunction materials were successfully prepared by the ultrasonic-assisted coprecipitation method. The Bi@BiOCl/C3N4-DPY heterojunction exhibited remarkable photocatalytic activity under visible light irradiation, and the degradation rate of methyl orange (MO) was about 90.6% in 180 min. This impressive efficiency is mainly due to the Z-Scheme charge transfer mechanism in Bi@BiOCl/C3N4-DPY, resulting in the efficient separation of charge carriers and an increase in the REDOX potential of photogenerated electrons and holes. C3N4 was modified with a π-deficient conjugated pyridine ring, which caused the light absorption redshift, promoted the formation of oxidizing •O2-, and improved the photocatalytic activity. At the same time, a well-aligned heterojunction is formed at the interface between C3N4-DPY and BiOCl, facilitating the seamless transfer of light-induced electrons from the LUMO of C3N4-DPY to the CB of BiOCl. In addition, the addition of Bi introduces a unique band gap reduction effect, resulting in a change in the density of the band states, which further promotes charge transfer and separation. It is worth noting that the introduction of metallic bismuth (Bi) brings about a unique band gap reduction effect, resulting in a change in the density of states within the band, which ultimately promotes charge transfer and separation. The Z-scheme charge migration inside Bi@BiOCl/C3N4-DPY further promotes the efficient separation of photogenerated electron-hole pairs, greatly improving the overall efficiency of the material. The Z-structured photocatalyst developed in this study has great application potential in various fields of photocatalysis